The community as an active part in the implementation of interventions for the prevention and care of tuberculosis: A scoping review. - Lesly Chavez-Rimache; César Ugarte-Gil; Maria J Brunette (PLOS Global Public Health)
Interventions involving direct community stakeholders include a variety of approaches in which members take an active role in improving their health. We evaluated studies in which the community has actively participated to strengthen tuberculosis prevention and care programs. A literature search was performed in Pubmed, Scopus, ERIC, Global Index Medicus, Scielo, Cochrane Library, LILACS, Google Scholar, speciality journals, and other bibliographic references. The primary question for this review was: ¿what is known about tuberculosis control interventions and programs in which the community has been an active part?. Two reviewers performed the search, screening, and selection of studies independently. In cases of discrepancies over the eligibility of an article, it was resolved by consensus. 130 studies were selected, of which 68.47% (n = 89/130) were published after 2010. The studies were conducted in Africa (44.62%), the Americas (22.31%) and Southeast Asia (19.23%). It was found that 20% (n = 26/130) of the studies evaluated the participation of the community in the detection/active search of cases, 20.77% (n = 27/130) in the promotion/prevention of tuberculosis; 23.07% (n = 30/130) in identifying barriers to treatment, 46.15% (n = 60/130) in supervision during treatment and 3.08% (n = 4/130) in social support for patient. Community participation not only strengthens the capacities of health systems for the prevention and care of tuberculosis, but also allows a better understanding of the disease from the perspective of the patient and the affected community by identifying barriers and difficulties through of the tuberculosis care cascade. Engaging key community stakeholders in co-creating solutions offers a critical pathway for local governments to eradicate TB.